Working time and work-life balance in European companies establishment survey on working time 2004-2005 - Riedmann, Arnold; Bielenski, Harald; Szczurowska, Teresa; Wagner, Alexandra; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2006)
Working time arrangements and work-life balance are important issues on the European Union's political agenda. As defined at the Lisbon summit, increasing Europe's employment rates has become a major objective of the European Employment Strategy (EES), and working time can play an important role in this context. On the one hand, flexible working time arrangements are considered a means for improving the competitiveness of companies and national economies. On the other hand, there is a need to improve job opportunities for those groups experiencing particularly low employment rates: for example, in some European countries, women (particularly if they have to care for children) and older members of the workforce. In order to reach this objective, governments are being encouraged to develop childcare facilities (the Barcelona targets) and to implement policies facilitating greater reconciliation between work and family life. In this context, improving living and working conditions has become a major objective for the European institutions.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Labor laws and legislation -- European Union countries; Part-time employment -- European Union countries; Employment -- European Union; Electronic books